UDK 662.997÷621.47 SIMULATION OF HEAT TRANSFER PROCESS IN ABSORBER CHANNELS - Nigmatov, Ulugbek (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2023)
Abstract. Objective. At present, the issues of systematization of the energy balance, the development of thermal and mathematical models, as well as the generalization of methods and computer programs for calculating photovoltaic thermal modules are relevant. Methods. The program “Comsol Multiphysics 5.6.” was used to simulate the process occurring inside the absorber. To describe the laminar motion of a liquid (water), a non-stationary system based on the Navier-Stokes equation and the [1] heat distribution equation was used. Results. This article describes a mathematical model of heat transfer in absorber channels developed using the «Comsol Multiphysics 5.6. program». The results are presented for determining the longitudinal flow velocity at various sections of the flow channel, heat distribution over time, as well as the heat distribution isoline and isotherm. Conclusion. Developed on the basis of the program «Comsol Multiphysics 5.6.» a simulation model of heat transfer from a photovoltaic battery to a heat absorber can be used to calculate heat and power supply systems. The use of a simulation model in the design of a heat and power supply system makes it possible to reduce the consumption of heat and electricity.